ESCHERICHIA COLI ON BALI CATTLE ACCORDING TO MATURITY LEVELS IN DIFFERENT GEOGRAPHICIES AREA AND IT’S PATTERN OF ANTIBIOTICS RESISTANCE - Gargita, I Gede; Besung, I Nengah Kerta; Tenden Rompis, Aida Louise (Buletin Veteriner Udayana; Vol. 10 No. 2 Agustus 2018DO - 10.24843/bulvet.2018.v10.i02.p10, 2018)
A Cross Sectional study to determine the prevalence of Escherichia coli on bali cattle respiratory tractbased on maturity level (calves, heifers, adult) and geographical location (highland and lowland) have been conducted. The isolation and identification of bacteria based on the method of Carter and Cole with slightly modification and antibiotic sensitivity test were performed using the disc diffusion method by Kirby and Bauer. E scherichia coli was isolated from 14 out of the 120 samples (11.66%).  Based on the maturity level, was found 7/120 (5.58%), 3/120 (2.50%), and 4/120 (3.33%) from calves, heifers, and adults, respectively. Meanwhile, based on the geographical location, 8/120 (6.66%) E. coli was isolated from the highland and the remains 6/120 (5.00%) from lowland. The antibiograms showed that 6/14 (42.85%), 3/14 (21.42%), and 5/14 (35.71%) of the isolates were resistant, intermediate, and sensitive to sulfamethoxazole, respectively. Whereas 4/14 (28.57%), 1/14 (7.14%), and 9/14 (64.28%) were resistant, intermediate, and sensitive to ampicillin. One isolate (7.14%) was resistant to oxytetracycline and the remains 13/14 (92.85%) were sensitive. Three isolates (21.42%) were sensitive to all tested antibiotics and one isolate (7.14%) resistant to all antibiotics.